Anti-TNF Therapy and Malignancy – A Critical Review. (1st June 2001) - Cohen, Roger B; Dittrich, Karen A
Abstract : The roles of tumour necrosis factor (TNF) and anti-TNF therapy in malignancy are reviewed, including an overview of baseline risk factors for malignancy in inflammatory diseases and the incidences of malignancies observed in clinical trials of an anti-TNF-a therapy, infliximab. The preclinical data and early clinical experience presented for infliximab do not provide evidence for a causal relationship between TNF-a antagonism and the development of lymphoid or nonlymphoid cancers.